PERANCANGAN START-UP BUSINESS E-COMMERCE “CREATEEZ” MENGGUNAKAN METODE DESIGN THINKING - Ramadhan, Dany; Kusumaningtyas, Dian; Sardanto, Rino (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
This research is a research and development research that aims to examine the design and test of an e-commerce website called Createez, a start-up that aims to empower independent designers and small or medium-sized brand owners by creating a platform to connect creators, marketplaces, and producer. Data collection techniques used in this study were using questionnaires and interviews. The design of Createez uses the design thinking method which is divided into stages: Emphatize, Define, Ideate, Prototype, and Testing. Model testing using Miro and Figma software. The results of this study indicate that the Design Thinking method is implemented in the design of the Createez website and in the testing phase of this website it can help overcome the problems of brand owners (creators) such as fulfillment management, capital, and product stock that is often left over.